PENGARUH TEMAN SEBAYA TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI SMPN 23 PONTIANAK SELATAN - Suparto Damianus; Aminuyati Aminuyati; FY Khosmas (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study was conducted at SMPN 23 South Pontianak were found that the motivation of learners in the learning IPS subject is low. It is marked by the phenomenon of many learners still lackluster in the following study like chatting with a partner, homework at school and late in collecting duties. This research uses descriptive quantitative research methods and approaches correlation with a sample of 30 students of class VII B. This study uses statistical test simple linear regression method of data used to examine the influence of peers to motivate learners by using questionnaires. conditions peers in class VII B SMP 23 South Pontianak  gained by 71.66% so that peers can be categorized to "good". the motivation of learners in class VII SMPN 23 South Pontianak obtained by 77.61% so the motivation of learners categorized as "Good". Peer influence on the motivation of learners obtained from R Square 0.603, so the contribution of the influence of peers on motivation to learn of 60.3% while the remaining 39.7% is influenced by her other factors not examined in this study. In this study the influence of peers on motivation to learn categorized pretty good.. In this study the influence of peers on motivation to learn categorized pretty good.Keywords: Influence of Peers,  Motivation, Social Science